Blockchain for Organizing Effective Grass-Roots Actions on a Global Commons: Saving the Planet - Ducrée, Jens; Etzrodt, Martin; Gordijn, Bert; Gravitt, Max; Bartling, Sönke; Walshe, Ray; Harrington, Tomás (Frontiers in Blockchain, 2020)
An overwhelming majority of experts has been flagging for decades that “Saving the Planet” requires immediate, persistent and drastic action to curb a variety of catastrophic risks over the 21st century. However, despite compelling evidence and a range of suggested solutions, transnational coordination of effective measures to protect our biosphere continues to fall short. To remedy, we propose a novel platform for addressing the central issue of affording trust, transparency and truth while minimizing administrative overheads. This will empower an even loosely organised, global grass-roots community to coordinate a large-scale project on a shared goal (“Commons”) spanning the digital and real world. The Web3 concept is based on the swiftly emerging “Blockchain” and related cryptographic, distributed and permissionless technologies. “Wisdom of the crowds” mechanisms involving competitive parallelisation and prediction markets are enabled by formalised reputation and staking to incentivise high-quality work, fair validation and best management practice. While these mechanisms have been (mostly separately) applied to science, business, governance, web, sensor, information and communication technologies (ICT), our integrative approach around Blockchain-enabled ‘operating principles and protocols’ sets the basis for designing novel forms of potentially crowdfunded Decentralised Autonomous Organisations (DAOs).